The effect of atmospheric deposition on potassium accumulation in several tree species as a biomonitor - Işınkaralar, Kaan; Erdem, Ramazan (Environmental Research and Technology, 2022)
Minimizing air, water, and soil pollution are very important for a sustainable environment. Particularly, ensuring the continuity of soil fertility without deteriorating the soil structure is very important. This objective can be achieved only by determining the physical, biological, and chemical properties of atmospheric deposition and taking the required measures in agricultural lands. Trees and plants reflect the soil quality and especially they take both beneficial and harmful materials in their bodies owing to Saharan dust and using fossil fuel. Among them, nutrient elements have specific importance since it was determined that many factors including texture, irrigation method, organic matter, lime concentration, plant species and age, pH, and ion balance play effective roles in the growth or degradation of plants’ productivity. Being one of the major nutrient elements taken by plants, potassium (K+) is of vital importance for trees and plants. Its concentration, which varies depending on the species of plant, is influenced by the mutual interaction between tree development and environmental/genetic factors. The scope of this study was to evaluate and rank the contribution of atmospheric potassium (K+) deposition flows to organs of Robinia pseudoacacia L., Cupressus arizonica G., and Platanus orientalis L. trees as biomonitors.
Keywords: Environmental Engineering; Çevre Mühendisliği; Atmospheric deposition; biomonitors; nutrient element potassium; trees; 2. Zero hunger; 13. Climate action; 15. Life on land; 6. Clean water